Thermodynamic study of HPLC enantioseparations of some sulfur-containing amino acids on teicoplanin columns in ion-pairing reversed-phase mode. Issue 16 (1st October 2016) - Bystrická, Zuzana; Bystrický, Roman; Lehotay, Jozef
ABSTRACT: Homocysteine is an essential amino acid produced in the metabolism of methionine. It can be regulated through two metabolic routes either to cysteine or back to methionine. The imbalance in the methionine or homocysteine metabolism is connected with many disorders. In this work, HPLC enantioseparations of cysteine, homocysteine, and methionine were performed. Enantiomers were separated on natural teicoplanin and teicoplanin aglycone chiral stationary phases when buffered mobile phase with the presence of an ion-interaction reagent was used. The column temperature effect on the enantiomeric retention, selectivity, and resolution was studied in the range of 5–45°C at 5°C increment. Thermal stability of homocysteine standard was investigated by X-ray powder-diffraction measurements at elevated temperature in the range of 25–100°C at 5°C increment in air. Moreover, the thermodynamic analysis was used to quantify contributions of entropic and enthalpic terms on separations of investigated amino acid enantiomers. The elution order of enantiomers was determined in all cases. GRAPHICAL ABSTRACT: